2013
DOI: 10.1161/atvbaha.113.301468
|View full text |Cite
|
Sign up to set email alerts
|

Small, Dense High-Density Lipoprotein-3 Particles Are Enriched in Negatively Charged Phospholipids

Abstract: Objective— High-density lipoprotein (HDL) displays multiple atheroprotective activities and is highly heterogeneous in structure, composition, and function; the molecular determinants of atheroprotective functions of HDL are incompletely understood. Because phospholipids represent a major bioactive lipid component of HDL, we characterized the phosphosphingolipidome of major normolipidemic HDL subpopulations and related it to HDL functionality. Approach and Results—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
172
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 265 publications
(179 citation statements)
references
References 53 publications
7
172
0
Order By: Relevance
“…The pioneering study of Wiesner and colleagues published in 2009 (Wiesner et al 2009) provided reference values for the lipidome of HDL isolated from healthy normolipidemic controls by FPLC. In an attempt to further characterise HDL composition and address its inherent heterogeneity, we recently reported the phospho-and sphingolipidome of five major HDL subpopulations isolated from healthy normolipidemic subjects (Camont et al 2013). …”
Section: Lipidomementioning
confidence: 99%
“…The pioneering study of Wiesner and colleagues published in 2009 (Wiesner et al 2009) provided reference values for the lipidome of HDL isolated from healthy normolipidemic controls by FPLC. In an attempt to further characterise HDL composition and address its inherent heterogeneity, we recently reported the phospho-and sphingolipidome of five major HDL subpopulations isolated from healthy normolipidemic subjects (Camont et al 2013). …”
Section: Lipidomementioning
confidence: 99%
“…91 In fact, most of the phosholipid molecular species identified by liquid-chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) profiling of HDL particles could be linked to an atheroprotective biological activity of HDL. 86 Especially, a strong relationship existed between the content of negatively charged phosphatidylserine and various metrics of HDL function, i.e. the cholesterol efflux capacity from THP-1 cells, the anti-oxidative activity towards LDL, the ability to counteract platelet activation, the anti-inflammatory properties in a cell-free assay, and the potential to protect endothelial cells from apoptosis.…”
Section: Glycerophospholipidsmentioning
confidence: 99%
“…the cholesterol efflux capacity from THP-1 cells, the anti-oxidative activity towards LDL, the ability to counteract platelet activation, the anti-inflammatory properties in a cell-free assay, and the potential to protect endothelial cells from apoptosis. 86 Artificial enrichment of HDL3 with phosphatidylcholines increased SR-BI-mediated cholesterol efflux. 92 The same investigators subsequently showed that enhanced in vivo hydrolysis of HDL phospholipids by overexpression of endothelial lipase in human apoA-I transgenic mice caused pronounced reductions in the serum phospholipid/apoA-I ratio and attenuated the capacity of serum to mediate cholesterol efflux via SR-BI by 90%, whereas the ABCA1-dependent efflux potential increased by 63%.…”
Section: Glycerophospholipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower organic phases were dried in nitrogen, resuspended, and transferred into liquid chromatography-mass spectrometry (LC-MS) amber vials with inserts. LC-MS analysis and SM quantification were performed as previously described (17). The percentage of SM efflux was calculated as 100 3 (medium SM)/(medium SM + cell SM).…”
Section: Quantification Of Sm Massmentioning
confidence: 99%